Pontos de vista e representações discursivas: uma análise da narrativa em evangelhos sinóticos - Silva, Wendell Pereira da (2021)
In this research, biblical texts found in the synoptic gospels of Matthew and Luke are analyzed, considering common events narrated by these two authors. This study focuses on inquiring into the syntactic-semantic choices made by each narrator and seeks to interpret the different discursive constructions shown by the evangelists in accomplishing their texts. Although considered synoptic (which means “same vision” gospels), the aforementioned Gospels are believed to bear their author’s hallmarks, which bring different meanings in specific “co(n)texts”, and this can be noticed in the way their writers choose to present a certain character. This research is based on the textual linguistic postulates by Koch (2015, 2016, 2018) and Marcuschi (2008, 2012); with a special focus on Adam’s studies of Textual Discourse Analysis (2008, 2017, 2019) and on Rabatel’s theory (2009, 2016, 2019) on points of view. Therefore, the textual analysis made in this dissertation seeks to identify different points of view presented in the Gospel narratives in order to discover whether they can be used as signs for an interpretation of a psychosocial and cultural reality of the authors/enunciators. The concept of discursive representations, conceived by Adam (2008) and discussed by Rodrigues (2014), Rodrigues et al. (2010, 2012) and Passeggi (2001), was also added to this research to allow a (re)construction of significant discursive representations of the semantic universe of the evangelists. The analyses reveal that, despite depicting the same events, evangelists elicit, through active characters, different points of view in their texts, which corroborate for the construction of several discursive images that can disclose a lot of the Gospel narrative universe. Luke’s narrative, for example, when compared to that of Matthew, provides quiet a greater visibility to women’s point of view, when they are present in the narrative, emphasizing their perspective. Furthermore, his narrative promotes the construction of the representation of the Messiah based on his strength and his humanity. Matthew’s narrative, on the other hand, unveils a representation of the opponents to Jesus’ mission as weak enemies before the Messiah’s strength, and this is done by attributing negative semantic traits to them. The textual and discursive analysis of the synoptic Gospels, in accordance with the theoretical grounds in this dissertation, works with a broad and complex object, which is totally useful for an approach that treats the Bible mostly as a text, but nevertheless respects the symbolic importance of the Sacred Scripture.